Mineral nutrition of Cyclanthera pedata - Fernandes, Luiz Arnaldo; Alves, Daniel Soares; Ramos, Sílvio Junio; de Oliveira, Fernanda Ataíde; da Costa, Cândido Alves; Martins, Ernane Ronie (Pesquisa Agropecuaria Brasileira, 2005)
<!--[if gte mso 9]> Normal 0 <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> The objective of this work was to characterize the nutritional limitations for dry matter production of Cyclanthera pedata (L.) Schrad. Two successive cultivations were conducted in 3 dm3 pots with soil. The experimental design was totally randomized with 13 treatments and three replications. Treatments were based on the missing element technique (with omission of liming and each one of the macro and micronutrients). Cyclanthera pedata plants have their dry matter production reduced by soil acidity and low macronutrients availability, mainly P, Ca, Mg and S, and were little affected by low micronutrients availability.